Psychotic Experiences and Hikikomori in a Nationally Representative Sample of Adult Community Residents in Japan: A Cross-Sectional Study - Yasuma, Naonori; Watanabe, Kazuhiro; Nishi, Daisuke; Ishikawa, Hanako; Tachimori, Hisateru; Takeshima, Tadashi; Umeda, Maki; Kawakami, Norito (Frontiers in Psychiatry, 2021)
Psychotic experiences (PEs) may be associated with hikikomori. In the present study, we analyzed interview data from a community-based representative sample (N=1,616) in Japan to know the association of PEs, as well as the two components, i.e., hallucinatory experiences (HEs) and delusional experiences (DEs), with lifetime experience of hikikomori . Multivariate logistic regression analysis was used to estimate the association between any PE, HE, and DE, and hikikomori, adjusting for socio-demographics and other psychopathologies (mental disorder in the past 12 months and autistic spectrum disorder traits). Any PE was significantly associated with hikikomori (odds ratio (OR) =3.44, 95% CI= 1.14-10.33) after adjustment for sociodemographic factors, while the association attenuated after adjusting for other psychopathologies. Any DE remained significantly associated with hikikomori, even after adjustment for all the covariates (OR=10.50, 95% CI= 1.57-70.29). Any HE was not significantly associated with hikikomori. It is suggested that DEs are associated with hikikomori, independent of other psychopathology. A future study is need to examine a temporal relationship in the association between DEs and hikikomori.